- #1

- 5

- 0

## Homework Statement

Suppose f(x,y) = 2x^5 + 4xy + 2y^3

g1(u,v) = u^2 - v^2

g2(u,v) = uv

h(u,v) = f(g1(u,v), g2(u,v))

Use chain rule to calculate:

dh/du (1,-1) and dh/dv (1,-1)

## Homework Equations

## The Attempt at a Solution

i let h (u,v) = 2(u^2 - v^2)^5 + 4(u^2-v^2)(uv) + 2(u-v)^3

then i tried drawing a chain rule tree diagram:

h --> f --> g1 and g2

g1 --> x and y

g2 --> x and y

so dh/du = (dh/df . df/dx . dx/du) + (dh/df . df/dy . dy/du)

then i got stuck :S

help please?